Optimal Adaptation Period for Metabolic Cage Experiments in Mice at Different Developmental Stages - TAN He; YANG Xiaohui; ZHANG Daxiu; WANG Guicheng (Shiyan dongwu yu bijiao yixue)
Objective To investigate the optimal adaptation period for mice at different developmental stages during metabolic cage experiments, aiming to provide a reference for conducting metabolic research using mice. Methods A total of 80 male C57BL/6J mice at three developmental stages (weaning period M1, adolescent M2, and adulthood M3) were subjected to a 7-day metabolic cage experiment. Data on food intake, water intake, energy expenditure, respiratory quotient, body weight, and activity levels were recorded every five minutes. The collected data were processed using time series decomposition and comprehensive cluster analysis. Statistical differences were compared using repeated measures ANOVA combined with t-test to determine the optimal adaptation period. Results Significant differences in metabolism were observed among mice in different developmental stages (P<0.01). Compared with adolescent (M2) and adult (M3) mice, weaned mice (M1) exhibited lower activity level (P<0.01) and less distinct circadian rhythm. M1 mice had higher oxygen consumption, carbon dioxide production, and energy expenditure, as well as a lower respiratory quotient (all P<0.001), indicating that they mainly relied on fat as an energy source. Analysis of food intake, water intake, and energy expenditure revealed significant differences between the first light cycle (0-12 h) and the second light cycle (24-36 h) across all developmental stages (all P<0.05) . However, there was no significant difference in daily food intake or water intake after 24 hours (both P>0.05). Comprehensive cluster analysis of multiple indicators showed that the overall indicators of mice during the first 24 hours in the metabolic cages did not cluster with those of the subsequent 6 days, demonstrating significant differences. Conclusion Metabolic cage experiment can be used to detect continuous physiological changes in mice. The results suggest that mice can adapt to new metabolic cages environment within 24 hours, providing a theoretical basis for the design of metabolic experiments using mice.